Lunate morphology: association with the severity of scapholunate ligament injuries and carpal instability patterns. Issue 3 (1st June 2022) - Rachunek, Katarzyna; Springer, Fabian; Barczak, Maja; Wahler, Theodora; Daigeler, Adrien; Medved, Fabian
Abstract: Type II lunate has been associated with a lower incidence of dorsal intercalated segment instability (DISI) in the case of scapholunate dissociation. We aimed to evaluate the frequency of different lunate types and their influence on the prevalence and severity of scapholunate ligament (SLIL) injuries and the development of DISI. The surgical records of 414 arthroscopies were reviewed retrospectively. Lunate types were diagnosed based on radiograms and MRI examinations. The Type II lunate had a facet between hamate and lunate; in the Type I lunate, this facet is lacking. We additionally included the assessment of the capitate–triquetrum distance (CTD), which defines Type I, Intermediate, and Type II lunates. We adopted the DISI when the scapholunate angle was more than 80° and/or the radiolunate angle less than −15°. Fisher's exact test was applied to compare the distribution frequency of SLIL lesions and DISI deformity of patients with different lunate types. To quantify the inter- and the intra-rater reliability of lunate type assessment Cohen's kappa was calculated and, for CTD measurements, a Bland–Altman plot was created. Up to 77.1% patients had Type II lunates. Regarding MRI and CTD classification in patients with Type I lunates, Grade 4 SLIL injuries were more common than in those with Intermediate and Type II ( p  < 0.05). In the case of Grade 4 SLIL lesions, DISI was more common in patients with Type I lunates ( p  < 0.05). There were, however, only 25 patients with Type I lunates, and Grade 4 SLIL lesions according to MRI, and 6 according to CTD measurement.